A Fully Soft and Passive Assistive Device to Lower the Metabolic Cost of Sit-to-Stand - Lee, Hangil; Kim, Seok Hee; Park, Hyung-Soon (Frontiers in Bioengineering and Biotechnology, 2020)
Various assistive devices like exoskeletons have been developed to aid the growing number of disabled people. Recent studies have started to explore using soft rather than rigid components to create lightweight and unobtrusive systems that can be more easily adopted by the general population. However, there is a tradeoff between compliance and power in these systems. We investigated the physiological benefits of using an inconspicuous, soft and passive assistive device which would avoid bulkiness, heaviness and user discomfort. We chose to assist the sit-to-stand (STS) maneuver because it is a common activity of daily living (ADL). STS is also recognized as one of the most challenging ADLs due to the high knee torque required, and the primary limiting factor is known to be knee extensor strength. Thus, the objective of this research was to develop and evaluate an unobtrusive knee assist wear called X-tights that could aid knee extension during STS using only soft and passive components. This was accomplished by routing elastic bands across the lower extremity. Thirty-one healthy participants performed STS tests with and without the X-tights, while metabolic cost and muscle activity were recorded. Metabolic power significantly decreased, by 3.2 ± 1.5% (P = 0.04), when utilizing the X-tights during the STS, while there was no statistically significant differences in muscle activity. The present work introduces a new soft and passive assist wear that can be worn inconspicuously under normal clothing, and we demonstrate promising results for the future development and integration of soft assistive technology for daily life.